Monitoring the technical condition of the fuel storage facility at the Ukrainian Antarctic Akademik Vernadsky station - Posypaiko, Yu.; Andreev, A. (Ukrainian Antarctic Journal, 2023)
The paper examines the technical condition of metal structures of the fuel storage facility and pipelines at the Ukrainian Antarctic Akademik Vernadsky station, the development and implementation of measures to increase the reliability of their work, and the organization of their regular annual monitoring. At the preparatory stage, the analysis of design and operational documentation for fuel storage facility VST-200 was performed, technical inspection methods were selected (ultrasonic thickness measurement, tightness control, visual and eddy current control, level and theodolite surveys, and others), equipment and auxiliary equipment were selected for performing diagnostic work by non-destructive testing methods (flaw-detectors, thickness gauge, leak detector, level, theodolite, and others). An instrumental inspection of the condition of metal structures of the double-skinned fuel storage tank VST-200 and pipelines was carried out using non-destructive testing methods to detect defects and damage in structural elements and welded joints, as well as inspection of the condition of the foundation and base of the tank. Anti-corrosion work was carried out on the bottom of the station’s fuel tank VST-200, and pipelines with corrosion damage were replaced. All elements (foundations, walls, bottoms, and roofs of the external and internal reservoirs) are in working technical condition. They meet the norms and standards for design, manufacture, and operation. The static strength of the walls of both reservoirs is adequate for the project and current regulations. Thanks to the anti-corrosion work on the bottom of the internal tank, it is possible to continue its operation until 2029 by providing the rules of the technical operation of the fuel storage facilities and the organization of annual monitoring of the technical condition of the tank and technological equipment. The old decommissioned fuel storage tank HST-150 is modified into a dry solid materials store.